2016
DOI: 10.1590/1678-4162-8795
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated drinking water for lightweight laying hens

Abstract: The study aimed to evaluate the effect of different levels of chlorine in drinking water of laying hens on zootechnical performance, eggs shell quality, hemogasometry levels and calcium content in tibia. 144 HyLine laying hens, 61 weeks old, were used distributed in 24 metabolism cages. They were subjected to water diets, for a period of 28 days, using sodium hypochlorite as a chlorine source in order to obtain the following concentrations: 5ppm (control), 20ppm, 50ppm, and 100ppm. Their performance was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…Lima et al (2015) observed similar results in quail eggs when researching different levels of sodium in the feed. Schneider et al (2016) did not observe differences in production, weight or specific gravity of eggs of laying hens consuming increasing levels of sodium (5 to 100 ppm). Specific gravity was not influenced by the ambient temperature (Table 2), with averages of 1.06g cm -3 , similar to those mentioned by Silva et al (2017).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Lima et al (2015) observed similar results in quail eggs when researching different levels of sodium in the feed. Schneider et al (2016) did not observe differences in production, weight or specific gravity of eggs of laying hens consuming increasing levels of sodium (5 to 100 ppm). Specific gravity was not influenced by the ambient temperature (Table 2), with averages of 1.06g cm -3 , similar to those mentioned by Silva et al (2017).…”
Section: Resultsmentioning
confidence: 55%
“…It is ideal to provide birds with water with a salinity of up to 1.5 dS m-1. Quails are tolerant of the consumption of more saline water (Raquel et al, 2011;Lima et al, 2015;Petrucci et al, 2017;Lima, Moraes, & Barreto, 2020) but at high levels, metabolic and consumption alterations may occur, affecting the production and quality of eggs (Petrucci et al, 2017;Schneider et al, 2016). In addition, excessive intake of minerals increases water consumption and reduces the glomerular filtration rate in the kidneys, leading to increased renal excretion, which will be rich in minerals, such as sodium, chlorine and potassium (Freitas et al, 2013;Alahgholi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Meng et al (2023) melaporkan bahwa ayam ras pedaging yang mengkonsumsi air dengan konsentrasi klorin bebas 0,86 mg/L tidak akan mengganggu kerja permukaan saluran pencernaan. Berdasarkan tulisan Schneider et al (2016) batas kandungan klorin dalam air minum ayam ras yaitu sebanyak 5 ppm.…”
Section: Pendahuluanunclassified
“…Rekomendasi konsentrasi klorin pada air minum ayam ras yang dilaporkan peneliti terdahulu berkisar 3-5 ppm (Schneider et al, 2016;Jacobs et al, 2020;Rossi et al, 2021). Berdasarkan rekomendasi tersebut, maka hasil pengamatan dikelompokkan menjadi 3 kategori seperti pada Gambar 1.…”
Section: Level Penggunaan Kaporit Pada Kandang Ayam Ras Pedagingunclassified